Left ventricular global longitudinal strain in patients with heart failure with preserved ejection fraction: outcomes following an acute heart failure hospitalization. (20th April 2017) - Buggey, Jonathan; Alenezi, Fawaz; Yoon, Hyun Ju; Phelan, Matthew; DeVore, Adam D.; Khouri, Michel G.; Schulte, Phillip J.; Velazquez, Eric J.
Abstract: Aims: While abnormal resting LV GLS has been described in patients with chronic heart failure with preserved ejection fraction (HFpEF), its prognostic significance when measured during an acute heart failure hospitalization remains unclear. We assessed the association between left ventricular global longitudinal strain (LV GLS) and outcomes in patients hospitalized with acute HFpEF. Methods and results: We studied patients discharged alive for acute HFpEF from Duke University Medical Center between 2007 and 2010. Among patients with measurable LV GLS, we performed 2D, speckle‐tracking analysis and Cox proportional hazards models assessed the association between continuous LV GLS and outcomes. Baseline characteristics were stratified by normal (≤−16%) or abnormal (>−16%) LV GLS for comparison. Among 463 patients, the median LV GLS was −12.8% (Interquartile range, −15.8 to −10.8%) and was abnormal in 352 (76%). Overall patients in the cohort were generally elderly, female and had hypertension. After multivariable adjustment, worse outcomes were noted between LV GLS and mortality (HR 1.19 per 1% increase; 95% CI 1.00–1.42; P = 0.046) and a composite endpoint of mortality or rehospitalization at 30 days (HR 1.08 per 1% increase; 95% CI 0.99–1.18; P = 0.08). There was no association between LV GLS and mortality or a composite of mortality or rehospitalization at 1 year. Conclusions: A high prevalence of patients hospitalized with acute HFpEF have abnormal LV GLS suggesting unrecognized myocardial systolic dysfunction. Furthermore, worse LV GLS is associated with worse clinical outcomes at 30 days but not by1 year.